The Electromagnetic Interference Model Analysis of the Power Switching Devices - Zhang Wei (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The switching device turn-on and turn-off process will produce high-frequency electromagnetic interference, based on the finite element method ANSYS software with powerful computing capabilities, has been widely used in complex electromagnetic field calculations. In this paper, ANSYS software to model and analyze the insulated gate bipolar transistor (IGBT) and quantitative distribution of electromagnetic interference (EMI), and for the staff and scientists doing research in electromagnetic field analysis provides an effective reference program. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1884